Chapter 2: The Courage and Moral Choice Project: Maine, Phase 2 - Baruch, Adele (Narrative Works, 2020)
Phase 2 of the Courage and Moral Choice Project (CMCP) involved a more structured and planned learning experience than had Phase 1. Two teachers at an alternative public high school collaborated with researchers and artist educators to develop an integrated, three-month learning experience around stories of helping. Students participated on a voluntary basis and focused on these stories through language arts, history, art, and service learning experiences. They were encouraged to tell their own stories of courageous moral choices, and their exchanges led to more general disclosure and trust in the learning environment. Artist educators were brought into the schools to encourage students to translate their experiences of moral choice into poetry, essays, art, and songs. Teachers and students reported a more cohesive sense of community as well as increased empathy and awareness of the help of others among participants. Keywords: interpersonal trust, expanded generosity, artist educators